Evidence linking oxidative stress, mitochondrial dysfunction, and inflammation in the brain of individuals with autism - Rossignol, Daniel A.; Frye, Richard E. (Frontiers in Physiology, 2014)
Autism spectrum disorders (ASDs) are a heterogeneous group of neurodevelopmental disorders that are defined solely on the basis of behavioral observations. Therefore, ASD has traditionally been framed as a behavioral disorder. However, evidence is accumulating that ASD is characterized by certain physiological abnormalities, including oxidative stress, mitochondrial dysfunction and immune dysregulation/inflammation. While these abnormalities have been reported in studies that have examined peripheral biomarkers such as blood and urine, more recent studies have also reported these abnormalities in brain tissue derived from individuals diagnosed with ASD as compared to brain tissue derived from control individuals. A majority of these brain tissue studies have been published since 2010. The brain regions found to contain these physiological abnormalities in individuals with ASD are involved in speech and auditory processing, social behavior, memory, and sensory and motor coordination. This manuscript examines the evidence linking oxidative stress, mitochondrial dysfunction and immune dysregulation/inflammation in the brain of ASD individuals, suggesting that ASD has a clear biological basis with features of known medical disorders. This understanding may lead to new testing and treatment strategies in individuals with ASD.